Delta Infection After Vaccination Elicits Potent Neutralizing Immunity Against Severe Acute Respiratory Syndrome Coronavirus 2 Omicron . (16th April 2022) - Zhu, Ka-Li; Gao, Hui-Xia; Yao, Lin; Rong, Jun; Yang, Li; Zhang, Zhi; Jiang, Ping; Duan, Li-Jun; Wang, Guo-Lin; Dai, Er-Hei; Ma, Mai-Juan
Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) Omicron (B.1.1.529) variant extensively escape neutralizing antibodies by vaccines or infection. We assessed serum neutralizing activity in sera from Delta infection after vaccination and Delta infection only against SARS-CoV-2 Wuhan-Hu-1 (WA1), Beta, Delta, and Omicron. Sera from Delta infection only could neutralize WA1 and Delta but almost completely lost capacity to neutralize Beta and Omicron. However, Delta infection after vaccination resulted in a significant increase of serum neutralizing activity against WA1, Beta, and Omicron. This study demonstrates that breakthrough infection of Delta substantially induced high potency humoral immune response against the Omicron variant and other emerged variants. Abstract : The sera from patients with the Delta infection only had less neutralizing activity to the Omicron, whereas the sera from patients with Delta infection after vaccination displayed potent neutralization to the Omicron variant.